Implant related neurological deficit - Zakaria@Mohamad, Zamzuri (2019)
Every invasive procedure performed across surgical specialties has the potential of various complications. In spinal surgery, various implant such as plate and screw were used to achieve fixation in both elective and emergent procedures. Pedicle screw was the main implant which was used in the most of the surgery such as fusion surgery and deformity correction surgery. However, pedicle screw insertion is still associated with certain degree of complications despite technical advancement, knowledge and experience of the surgeon. Neurological deficit is one of the complications reported in various literature reviews. The overall incidence nerve root or spinal cord injury due to screw malpositioning ranges between 0.6% to 11%. Meticulous attention to detail with the placement of implant can limit its complications.